Inhibition of Trichophyton rubrum by 420-nm Intense Pulsed Light: In Vitro Activity and the Role of Nitric Oxide in Fungal Death - Huang, Hao; Huang, Meiling; Lv, Wenyi; Hu, Yong; Wang, Ruihua; Zheng, Xiufen; Ma, Yuetang; Chen, Chunmei; Tang, Hongfeng (Frontiers in Pharmacology, 2019)
Trichophyton rubrum is a common dermatophyte of the skin. The aim of this experiment was to explore the role of nitric oxide (NO) in the inhibition of T. rubrum growth induced by 420-nm intense pulsed light (IPL). This study found that nitric oxide synthase (NOS) and NO levels were increased whereas asymmetric dimethylarginine (ADMA) level, keratinase activity and fungal viability were decreased after IPL treatment compared with the control condition in vitro. Moreover, micromorphology was damaged by IPL treatment. Fungal viability was increased and the damage to the fungal structure was reduced after pretreatment with an NOS inhibitor (L-NMMA) compared with IPL treatment alone. Compared with IPL alone, pretreatment with L-NMMA decreased NOS expression and NO level and increased keratinase activity. We found that 420-nm IPL treatment can inhibit the growth of T. rubrum by regulating NO in vitro.